A hybrid method based on level set and 3D region growing for segmentation of the thoracic aorta. (23rd July 2013) - Martínez-Mera, Juan Antonio; Tahoces, Pablo G.; Carreira, José M.; Suárez-Cuenca, Jorge Juan; Souto, Miguel
Abstract: This study sought to develop a completely automatic method for image segmentation of the thoracic aorta. We used a total of 4682 images from 10 consecutive patients. The proposed method is based on the use of level set and region growing, automatically initialized using the Hough transform. The results obtained were compared to those of manual segmentation as performed by an external expert radiologist. Concordance between the developed method and manual segmentation ranged from 92.79 to 95.77% in the descending regions of the aorta and from 90.68 to 96.54% in the ascending regions, with a mean value of 93.83% being obtained for total segmentation.